2017
DOI: 10.1007/s00381-017-3342-0
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculoperitoneal shunt malfunction caused by fractures and disconnections over 10 years of follow-up

Abstract: Disconnection and fracture are two significant mechanical VP shunt dysfunctions and must be adequately researched and understood even during routine follow-ups. A disconnected or fractured shunt may be working and it is not safe to state that the shunt is no longer needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Other authors have reported that a disconnected portion of fractured shunt may be working and that it is not safe to state that the shunt is no longer needed. 11,28 In this way, we believe that the concept of arrested hydrocephalus should be treated with great care and that patients with catheter fractures, disconnections, or migrations should be carefully followed up with routine control examinations, and also that the ability of the family to access the hospital should be considered in the decision between surgical or conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported that a disconnected portion of fractured shunt may be working and that it is not safe to state that the shunt is no longer needed. 11,28 In this way, we believe that the concept of arrested hydrocephalus should be treated with great care and that patients with catheter fractures, disconnections, or migrations should be carefully followed up with routine control examinations, and also that the ability of the family to access the hospital should be considered in the decision between surgical or conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Shunt disconnection is the cause of malfunction in approximately 10% of cases. 1 Diagnosing shunt disconnection with shunt series X-rays may prove difficult as the disconnection may be subtle, as in our case, and the shunt may still be partially functional which can manifest as inconsistent and intermittent symptoms. 2,3 The negative predictive value of shunt series X-rays is only 22%.…”
mentioning
confidence: 80%
“…First, all observed patients were symptom‐free. In patients who suffered from cHC (eg, after meningitis or subarachnoid hemorrhage) years after the implantation of the shunt, the possibility of shunt independency should be acknowledged 28‐32 . The issue of NPH is even more complex.…”
Section: Discussionmentioning
confidence: 99%